Interdependence between business insurance and entrepreneurship and their impact on the economic growth - Vladimir Njegomir; Dragan Stojić; Jelena Demko-Rihter (Management, 2023)
Research Question: What type of mutual relations exist between business insurance and entrepreneurship, and how do they impact economic growth? Motivation: The primary motive for the research is the identified literature gap in the field of interdependence between business insurance and entrepreneurship and their joint contribution to economic growth. Idea: To test whether the interdependence between business insurance and entrepreneurship exists and their combined contribution to economic growth. The following independent variables were used: premium per entrepreneur, solved claims per entrepreneur, total technical reserves, GDP/p.c., a measure of demographic variables in the form of education level, a measure of the impact of banking, and the measure for institutional factors in terms of establishment costs the number of entrepreneurs by years as the dependent variable was considered. Data: Data were gathered from various sources (Serbian Statistical Office, National Bank of Serbia, World Bank) in the period from 2008 to 2019. Tools: Descriptive statistics, regression analysis, and statistical tests. Findings: The presented results show that there is a significant influence of insurance, both through insurance premiums per entrepreneur, which are paid to ensure the safety of the entrepreneur, and through resolved claims per entrepreneur, which present an indicator of insurance compensation in the case of damage to the entrepreneur, and through the impact of insurance on financial market by the amount of technical reserves. The return influence was not confirmed, considering that the number of entrepreneurs per year is a stationary variable, so the effect of the number of entrepreneurs on the development of insurance, measured by the premium per entrepreneur, could not be confirmed. Contribution: This research conducted in Serbia, a developing and upper middle-income country, confirmed the positive impact of insurance on entrepreneurship, but the return influence of entrepreneurship on insurance was not proven.